An early Phase II randomised controlled trial testing the effect on persecutory delusions of using CBT to reduce negative cognitions about the self: The potential benefits of enhancing self confidence - Freeman, D; Pugh, K; Dunn, G; Evans, N; Sheaves, B; Waite, F; Cernis, E; Lister, R; Fowler, D (Elsevier, 2014)
Background: Research has shown that paranoia may directly build on negative ideas about the self. Feeling inferior can lead to ideas of vulnerability. The clinical prediction is that decreasing negative self cognitions will reduce paranoia. Method: Thirty patients with persistent persecutory delusions were randomised to receive brief CBT in addition to standard care or to standard care (ISRCTN06118265). The six session intervention was designed to decrease negative, and increase positive, self cognitions. Assessments at baseline, 8 weeks (posttreatment) and 12 weeks were carried out by a rater blind to allocation. The primary outcomes were posttreatment scores for negative self beliefs and paranoia. Secondary outcomes were psychological well-being, positive beliefs about the self, persecutory delusions, social comparison, self-esteem, anxiety, and depression. Results: Trial recruitment and retention were feasible and the intervention highly acceptable to the patients. All patients provided follow-up data. Posttreatment there was a small reduction in negative self beliefs (Cohen's d = 0.24) and a moderate reduction in paranoia (d = 0.59), but these were not statistically significant. There were statistically significant improvements in psychological well-being (d = 1.16), positive beliefs about the self (d = 1.00), negative social comparison (d = 0.88), self-esteem (d = 0.62), and depression (d = 0.68). No improvements were maintained. No adverse events were associated with the intervention. Conclusions: The intervention produced short-term gains consistent with the prediction that improving cognitions about the self will reduce persecutory delusions. The improvement in psychological well-being is important in its own right. We recommend that the different elements of the intervention are tested separately and that the treatment is lengthened.